TINJAUAN BIM (BUILDING INFORMATION MODELLING) DALAM BIDANG ICT KONSTRUKSI DI NEGARA ASEAN - Wisnu Adi Prasetya (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This study discusses the current status of BIM implementation in ASEAN countries. Based on a review of recent research, this article focuses on the question of what is the current status of BIM implementation in ASEAN countries, and what further research is needed to advance the implementation of  BIM?  Addressing  these  questions  makes  researchers  and  practitioners focused on construction companies operating in ASEAN countries, seeking the benefits of BIM. Keywords: ICT, BIM, Building Information Modelling, Construction, ASEAN